Cost of Vagueness: Stakeholders' Responses to Firms' ESG Information - He, Hongbo (Journal of business ethics, 2025)
This paper examines the reactions of stakeholders to firms' ESG information and how these reactions impact firms’ financial performance. We further explore how firms' ESG performance and public attention moderate these relationships. Using a longitudinal dataset of Chinese listed firms from 2014 to 2023, we find that firms with vague ESG information are associated with increased financing constraints, diminished brand value, and reduced government environmental subsidies. Interestingly, these negative consequences are milder in firms with unusually poor ESG performance. Our findings also reveal that stakeholders' adverse responses deteriorate these firms' future performance. Moreover, public attention as an information intermediary is a double-edged sword: heightened public scrutiny alleviates stakeholders' negative reactions to vague ESG information but intensifies them when a firm's ESG performance is extremely poor. These results remain robust across alternative measures, models, and sample selection treatments. Overall, our study demonstrates that vague ESG information elicits adverse responses from stakeholders and weakens firm performance. These effects, however, are contingent upon a firm's ESG performance and the level of public attention it receives.